Deletion of human JK segments by site-specific recombination recognizing the conserved nonamer and heptamer sequences. - Nakatani, T (1990)
Mapping and partial sequencing of the productive K chain genomic DNA of FK-001 demonstrated a 1.8-kb deletion including the JK2, JK3, JK4, and JK5 segments. This deletion occurred between the heptamer recombination signal sequence of the JK2 segment and the heptamer-like sequence located 1.8 kb downstream of the JK2 segment. The recombination reaction kept the reciprocally joined signal sequences on the chromosome and deleted the intervening DNA segment. The cloned FK-001 K chain gene was expressed efficiently in mouse myeloma cells, demonstrating that the 1.8-kb deleted region conferred no functions for gene expression.